Addressing the impact of tobacco and alcohol use on cancer-related health outcomes - Hang Zhou; Babalola Faseru; Farhad Islami; Nigar Nargis; Maria Elena Martinez; Roy A Jensen; S Gail Eckhardt; Roy S Herbst (JNCI: Journal of the National Cancer Institute, 2026)
Abstract Tobacco and alcohol use are significant modifiable risk factors contributing to cancer morbidity and mortality globally. Recognizing the synergistic effects of these substances and their implications for cancer prevention and treatment, a national workshop titled “Addressing the Impact of Tobacco and Alcohol Use on Cancer-Related Health Outcomes” was convened in Washington, DC, in March 2025. This workshop brought together leading researchers in behavioral, basic, and clinical sciences, clinicians, public health practitioners, health economists, policymakers, patient advocates, and community stakeholders to review current evidence, identify gaps in practice and policy, and develop actionable recommendations. The goal of the workshop was to examine the evidence linking tobacco and alcohol use to cancer incidence and outcomes and to explore strategies for reducing their use to lower cancer risk and improve health outcomes. This commentary summarizes key themes from five sessions, including epidemiological insights, lessons from tobacco control policy, opportunities for alcohol policy, evidence-based cessation interventions, and strategies to address stigma and gaps in research and practice. The workshop underscored the need for integrated public health strategies, informed by lessons learned from tobacco control, to mitigate the cancer burden attributable to tobacco and alcohol use.